The chemokine CXCL12 and its receptor CXCR4 are implicated in human seminoma metastasis. (15th March 2013) - McIver, S. C.; Loveland, K. L.; Roman, S. D.; Nixon, B.; Kitazawa, R.; McLaughlin, E. A.
Summary Seminoma and non‐seminoma tumours increasingly occur within the western population. These tumours originate from carcinoma in situ (CIS) cells, which arise from dysfunctional gonocytes. CXCL12 and its receptors, CXCR4 and CXCR7, have been implicated in migration, proliferation and survival of gonocytes and their precursors and progeny, primordial germ cells and spermatogonial stem cells respectively. We previously found evidence that several miRNA molecules predicted to modulate CXCR4 signalling are differentially expressed during the differentiation of gonocytes into spermatogonia in mice. Bioinformatic analysis predicted these miRNA to modulate CXCR4 signalling, leading us to hypothesize that CXCL12‐mediated CXCR4 signalling is involved in the disrupted differentiation of gonocytes that underpins CIS formation. Indeed, we detected CXCL12 in Sertoli cells of normal human testis, and relatively high expression in tumour stroma with concomitant weak staining in dispersed tumour cells. In contrast, CXCR4 was expressed in spermatogonial and meiotic germ cells of normal testis and in the majority of tumour cells. Quantitative RT‐PCR identified elevated CXCR4 transcript levels in seminoma compared with normal testis and to non‐seminoma, potentially reflecting the higher proportion of dysfunctional germ cells within seminomas. In the normal testis, expression of CXCR4 downstream signalling molecules phospho‐MEK1/2 and phospho‐ERK1/2 correlated with CXCR4/CXCL12 expression. Strikingly, this correlation was absent in seminoma and non‐seminoma samples, suggesting that CXCL12 signalling is disrupted. Proliferation rate and cell survival were not altered by CXCL12 in either seminoma (TCam‐2) or non‐seminoma (833ke) cell lines. However, CXCL12 exposure induced TCam‐2 cell invasion though simulated basement membrane, while in contrast, we provide the novel evidence that CXCR4‐expressing non‐seminoma cell lines 833ke and NTera2/D1 do not invade in response to CXCL12. These findings indicate that CXCL12 expression in the human testis may selectively influence seminoma migration and metastasis, correlating with its importance in gonocyte and spermatogonial stem cell biology.